NAT.SCI. Park : a natural science exploration museum park complex, Barangay Sungay - East, Tagaytay City - Antonio, Lawrence John M. (Manila : National University, 2016)
Learning by experience can contribute not only on additional information but the progress of experiencing the true essence of knowledge. It has beneficial to the mind and soul as both interactions will adapt by learning it and adapting it. Sadly, at present time people rely on technology for gathering information. They tend to forget the most meaningful way of learning knowledge. Nevertheless, National Geographic is a leading magazine, blogger, channel and industries in terms of educational purposes. They educated all their spectators from different ages and countries through televisions, magazines, and the internet. Nat Geo for short, have been conduction expedition educational programs and expedition exhibition throughout the globe. To address the needs, NAT GEO could provide a Learning Center & Museum as the solution for the programs, expeditions, and events. And thus, NAT GEO SCIENCE PARK: A Natural Science Exploration Museum Park Complex is proposed by the author.
Acknowledgment -- Certificate of endorsement -- List of figures, tables, graphs -- Abstract -- Chapter 1. The problem & its setting -- Chapter 2. Research methodologies -- Chapter 3. Terms of reference -- Chapter 4. Data gathering, collation & analysis of data -- Chapter 5. Design framework -- Chapter 6. Translations -- Chapter 7. Recommendations -- Annex -- Bibliography.
Includes bibliographical references.